International Conference on Eurasian Economies 2019 2019
DOI: 10.36880/c11.02349
|View full text |Cite
|
Sign up to set email alerts
|

Testing The Validity of The Phillips Curve for Turkey With Vector Autoregressive and Markov Switching Models on The Basis of Inflation and Unemployment

Abstract: In this study, we tested the validity of the Phillips Curve for Turkey. We used Markov Switching Model for examine the relationship between two variables in different regime periods, Engle Granger Causality Test for detect the causality between two variables, Johansen Cointegration Test for observe the long term equilibrium relationship and The Impulse Response Analysis and Variance Decomposition Analysis for investigate the explanatory effect of two variables on each other. As a result of the analysis, it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…As a result, this study has also concluded that the Phillips curve is invalid for Turkey in line with the period addressed and analyses conducted. This conclusion is similar to the conclusions reached in the studies carried out by Kuştepeli (2005), Önder (2006), Çatık et al (2008), Mangır and Erdoğan (2012), Tabar and Çetin (2016), Özçelik and Uslu (2017), Petek and Aysu (2017), Karacan (2018), andYılmaz et al (2019).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…As a result, this study has also concluded that the Phillips curve is invalid for Turkey in line with the period addressed and analyses conducted. This conclusion is similar to the conclusions reached in the studies carried out by Kuştepeli (2005), Önder (2006), Çatık et al (2008), Mangır and Erdoğan (2012), Tabar and Çetin (2016), Özçelik and Uslu (2017), Petek and Aysu (2017), Karacan (2018), andYılmaz et al (2019).…”
Section: Conclusion and Discussionsupporting
confidence: 89%